Residential choices and experiences of older adults : pathways to life quality - Krout, John A.; Wethington, Elaine (Springer, 2003)
Based on the Pathways to Life Quality longitudinal research study, this book explores the ways in which older adults' residential choices impact their health and well-being. The study examines the factors associated with life quality for persons living on their own in the local community, as well as those in various housing arrangements such as a continuing care retirement facility, adult home, income-subsidized housing, and senior apartments. Topics include plans and adjustment to moving; role identities; social relationships, participation, and integration; health and activity patterns; and.